2009
DOI: 10.1016/j.vetimm.2008.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Development of cell-mediated immunity to porcine circovirus type 2 (PCV2) in caesarean-derived, colostrum-deprived piglets

Abstract: The interaction between porcine circovirus type 2 (PCV2) and the pig immune system has been suggested to be a determinant event for the pathogenesis of postweaning multisystemic wasting syndrome (PMWS). To gain insight into the host immune mechanisms developed upon PCV2 infection, early innate and adaptive immune responses were examined in 1-week-old, caesarean-derived, colostrum-deprived piglets using a subclinical infection model of PCV2 in combination with lipopolysaccharide (LPS) as a potential immunostimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 29 publications
5
37
3
1
Order By: Relevance
“…While a detectable antibody response to PCV2 vaccination is a good predictor for successful vaccine administration, it is not necessary to confer protection to pigs. It has been demonstrated that pigs with no detectable humoral response after PCV2 vaccination were protected from subsequent challenge likely due to induction of cellular immunity [35], [36]. While in this study 4/9 VAC + CHAL pigs had detectable antibody titers at challenge, 8/9 VAC + CHAL were protected from subsequent PCV2d challenge and had significantly reduced PCV2d viremia and PCV2d nasal and fecal shedding compared to CHAL pigs indicating that Circovac® confers protection against PCV2d.…”
Section: Discussioncontrasting
confidence: 51%
“…While a detectable antibody response to PCV2 vaccination is a good predictor for successful vaccine administration, it is not necessary to confer protection to pigs. It has been demonstrated that pigs with no detectable humoral response after PCV2 vaccination were protected from subsequent challenge likely due to induction of cellular immunity [35], [36]. While in this study 4/9 VAC + CHAL pigs had detectable antibody titers at challenge, 8/9 VAC + CHAL were protected from subsequent PCV2d challenge and had significantly reduced PCV2d viremia and PCV2d nasal and fecal shedding compared to CHAL pigs indicating that Circovac® confers protection against PCV2d.…”
Section: Discussioncontrasting
confidence: 51%
“…As protection from PCVAD is induced by PCV2 vaccination (Beach & Meng, 2012;Kristensen et al, 2011;Martelli et al, 2011), it is plausible that, under field conditions, PCV2-specific T-cell immunity is most likely an essential and substantial component of protection from PCVAD. This conclusion is supported by results obtained in other studies (Fort et al, 2009b;Martelli et al, 2011). PCV2 neutralizing antibody titres were significantly different between animals of different aged but identical vaccination groups (P,0.05).…”
supporting
confidence: 87%
“…proteins. The intensity of the generated response differs using either the Cap protein or the whole 516 PCV as an in vitro stimulus; IFN-γ responses obtained by stimulating PBMC with the whole virus 517 are higher than with the Cap protein, suggesting that infected animals in which PCV2 is replicating 518 might respond strongly to other viral components different from the Cap protein (Fort et al, 2009b). 519…”
Section: Cell-mediated Immune Response To Pcv2-vaccination and Infectmentioning
confidence: 99%